1994
DOI: 10.1007/bf01711901
|View full text |Cite
|
Sign up to set email alerts
|

Hypocortisolaemia and adrenocortical responsiveness at onset of septic shock

Abstract: In septic shock, 'hypocortisolaemia' is not uncommon and does not predict a high mortality; adrenocortical hypo-responsiveness may be associated with poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
80
0
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(92 citation statements)
references
References 32 publications
7
80
0
5
Order By: Relevance
“…11,12,29,30 Our study shows a prevalence of relative adrenal insufficiency reaching 76% in a homogenous group of patients with cirrhosis presenting with septic shock. Several potential mechanisms have been postulated, including adrenal exhaustion, 31 inhibition of cortisol synthesis by tumour necrosis factor-α 32 and, less likely, adrenal hemorrhage. 29 Despite this high prevalence of relative adrenal insufficiency, our study showed no survival benefit with hydrocortisone therapy, although hemodynamic parameters improved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,29,30 Our study shows a prevalence of relative adrenal insufficiency reaching 76% in a homogenous group of patients with cirrhosis presenting with septic shock. Several potential mechanisms have been postulated, including adrenal exhaustion, 31 inhibition of cortisol synthesis by tumour necrosis factor-α 32 and, less likely, adrenal hemorrhage. 29 Despite this high prevalence of relative adrenal insufficiency, our study showed no survival benefit with hydrocortisone therapy, although hemodynamic parameters improved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with septic shock, a decreased response to the SST, namely, an absolute increment of the serum cortisol level less than 9 g/dL, is associated with an impaired vascular reactivity to vasopressors 5 and a high mortality. [5][6][7][8][9] Patients with cirrhosis share many similar hemodynamic features with patients with septic shock and adrenal insufficiency, namely, increased cardiac output, decreased peripheral vascular resistance, decreased mean arterial pressure, and hypo-responsiveness to vasopressors. 1,[10][11][12][13] Consistent with observations in septic patients, hemodynamic impairment is closely related to mortality and morbidity in patients with cirrhosis.…”
mentioning
confidence: 99%
“…Nevertheless, several studies have reported a high mortality associated with high cortisol levels thought to be a function of the underlying severe illness. 5,6,10,11,20,24 In this study, mortality rate was also extremely high among the patients with PAF. In a recent study of cortisol kinetics during and after cardiopulmonary arrest in the ED, it was noted that failure to attain a cortisol level of at least 30 g/dL was associated with 100% mortality at 24 hours.…”
Section: Discussionmentioning
confidence: 54%
“…Rothwell et al, 25 who evaluated a group of 32 patients in septic shock and adequate 24 also noted a positive correlation between decreased response to the ACTH stimulation and increased mortality; moreover, patients had a low probability of responsiveness to ACTH within the 24 hours preceding their deaths. Nevertheless, several studies have reported a high mortality associated with high cortisol levels thought to be a function of the underlying severe illness.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation